Lymphomatoid and Mediastinal Granulomatosis in 2-Year-Old Child - S.V. Vesely; I.P. Zhurilo; V.K. Litovka; K.V. Latyshov (Zaslavsky O.Yu., 2014)
Lymphomatoid granulomatosis in children is rare. The lungs are affected almost always, other extragonadal area are being affected frequently. Verification of the diagnosis is possible after puncture biopsy or surgery. Patient K., 2 years and 3 months old, was observed by us. This patient was admitted to hospital with a suspected tumor of the chest cavity from the right. Child suffers from primary combined immunodeficiency. Since November 2012 this girl is observed and is treated by a neurologist for progressive encephalitis with tetraparesis phenomena. Due to fever, cough and difficul swallowing, radiography of the chest was made 10.07.13. Neoplasm of the right chest cavity was detected on radiogram. The puncture biopsy to verify the diagnosis failed to do. Clinical diagnosis is an inflammatory pseudotumor of the chest cavity (mediastinum and lung) on the right. Mesenchymoma? Lymphoma? 24.07.13 the operation was performed: right thoracotomy, removal of the tumor of the upper lobe of right lung. Immunohistochemical examination results were received: lymphomatoid granulomatosis, grade II. The postoperative period was uneventful. Sutures are removed, the wound healed by primary intention. 10.08.13 the child was discharged home. Further treatment in Minsk (Belarus) is planned.